2006
DOI: 10.1179/174328106x101457
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation of non-metallic inclusions during casting of hot work die steel

Abstract: A chemical characterisation of the non-metallic inclusions in the aluminium killed tool steels during the casting process has been performed. The steel samples taken during the mould fillings, after casting and from the final products have been studied. The chemical compositions of the different phases in the inclusions have been analysed using SEM/EDX. Three types of inclusions, namely, type 6 (spinel surrounded by the calcium-aluminate oxide solution), type 7 (calcium-aluminate oxide solution) and type 9 (al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…An earlier study [26] at Uddeholm Tooling AB revealed eight types of inclusions during ladle treatment. In the present work, six of the eight types were detected.…”
Section: A Inclusions Found In the Industrial Samplesmentioning
confidence: 98%
See 1 more Smart Citation
“…An earlier study [26] at Uddeholm Tooling AB revealed eight types of inclusions during ladle treatment. In the present work, six of the eight types were detected.…”
Section: A Inclusions Found In the Industrial Samplesmentioning
confidence: 98%
“…[26] a LOM was more than 50,000 mm 2 . Approximately 30,000 of nonmetallic inclusions were found and examined.…”
Section: A Inclusions Found In the Industrial Samplesmentioning
confidence: 98%
“…After vacuum degassing, most of the inclusions were calcium aluminate liquid inclusions. 1,2,12) An example of these inclusions is presented in Fig. 6.…”
Section: Liquid Oxide Inclusions At the End Of Ladlementioning
confidence: 99%
“…Treatment In previous studies, 1,2,12) it was found that a large number of liquid inclusions of calcium aluminate coexist with spinel inclusions before vacuum degassing. After vacuum degassing, most of the inclusions were calcium aluminate liquid inclusions.…”
Section: Liquid Oxide Inclusions At the End Of Ladlementioning
confidence: 99%
See 1 more Smart Citation